Utilisation of blood products at a centre in Pakistan. Is donating better than wasting? - Haya Ul Mujtaba; Nida Anwar; Naveena Fatima; Imran Naseer; Munira Borhany; Tahir Shamsi (Journal of the Pakistan Medical Association, 2020)
Abstract The study was designed to investigate the quantity and reasons of wastage of blood products. This was an observational study conducted from February 2018 to February 2019 at the National Institute of Blood Disease and Bone Marrow Transplantation (NIBD and BMT), PECHS campus. The study was approved by the institutional review board. Wastage and reasons of wastage for all the blood products were evaluated. Frequencies were calculated by using SPSS version 23.0. A total of 2,880 bags of blood products were available, including 960 each of platelets, packed red cells and fresh frozen plasma. The overall wastage rate was 3.5%. Packed red cells and platelets were fully consumed, yet shortage of supply was observed. However, highest wastage was observed in fresh frozen plasma i.e. 102 bags. Expiry of unused products 60 (59%) followed by broken bags 30 (29%) were two common modes of wastage. Continuous...